Antiprotozoal and cysteine proteases inhibitory activity of dipeptidyl enoates. Issue 16 (1st September 2018) - Royo, Santiago; Schirmeister, Tanja; Kaiser, Marcel; Jung, Sascha; Rodríguez, Santiago; Bautista, José Manuel; González, Florenci V.
Graphical abstract: Abstract: A family of dipeptidyl enoates has been prepared and tested against the parasitic cysteine proteases rhodesain, cruzain and falcipain-2 related to sleeping sickness, Chagas disease and malaria, respectively. They have also been tested against human cathepsins B and L1 for selectivity. Dipeptidyl enoates resulted to be irreversible inhibitors of these enzymes. Some of the members of the family are very potent inhibitors of parasitic cysteine proteases displaying k2nd (M −1 s −1 ) values of seven orders of magnitude. In vivo antiprotozoal testing was also performed. Inhibitors exhibited IC50 values in the micromolar range against Plasmodium falciparum, Trypanosoma brucei, Trypanosoma cruzi and even more promising lower values against Leishmania donovanii .